ANALISIS KESULITAN DALAM MENYELESAIKAN SOAL MATERI BARISAN PADA SISWA SMA - Mita Wulandari; Wahyu Setiawan (IKIP Siliwangi, 2021)
This research was conducted to analyze the difficulties experienced by high school students when solving problems regarding the line material. The method used is descriptive qualitative research. This research was conducted at one of the public high schools in Karawang for the 2020-2021 academic year with the subjects of class XII totaling 26 students. The technique for collecting research data is by giving a test in the form of description questions, amounting to 6 questions with predetermined indicators. Data analysis was carried out, namely data reduction, data presentation and drawing conclusions. The results of the analysis show that (1) students with heterogeneous mathematical abilities still have difficulty understanding and solving problems regarding the sequence material; (2) the students' difficulties with the sequence material, namely the lack of understanding of the questions and formulas to be used; (3) the students' abilities in understanding a concept in the Line material still need to be explored or trained more deeply.